Clinical InvestigationsPerioperative high dose rate (HDR) brachytherapy in unresectable locally advanced pancreatic tumors - Waniczek, Dariusz; Piecuch, Jerzy; Rudzki, Marek; Mikusek, Wojciech; Arendt, Jerzy; Białas, Brygida (Journal of Contemporary Brachytherapy, 2011)
Purpose : The aim of the study was to present an original technique of catheter implantation for perioperative HDR-Ir192 brachytherapy in patients after palliative operations of unresectable locally advanced pancreatic tumors and to estimate the influence of perioperative HDR-Ir192 brachytherapy on pain relief in terminal pancreatic cancer patients. Material and methods : Eight patients with pancreatic tumors located in the head of pancreas underwent palliative operations with the use of HDR-Ir192 brachytherapy. All patients qualified for surgery reported pain of high intensity and had received narcotic painkillers prior to operation. During the last phase of the surgery, the Nucletron® catheters were implanted in patients to prepare them for later perioperative brachytherapy. Since the 6th day after surgery HDR brachytherapy was performed. Before each brachytherapy fraction the location of implants were checked using fluoroscopy. A fractional dose was 5 Gy and a total dose was 20 Gy in the area of radiation. A comparative study of two groups of patients (with and without brachytherapy) with stage III pancreatic cancer according to the TNM scale was taken in consideration. Results and Conclusions : The authors claim that the modification of catheter implantation using specially designed cannula, facilitates the process of inserting the catheter into the tumor, shortens the time needed for the procedure, and reduces the risk of complications. Mean survival time was 5.7 months. In the group of performed brachytherapy, the mean survival time was 6.7 months, while in the group of no brachytherapy performed – 4.4 months. In the group of brachytherapy, only one patient increased the dose of painkillers in the last month of his life. Remaining patients took constant doses of medicines. Perioperative HDR-Ir192 brachytherapy could be considered as a practical application of adjuvant therapy for pain relief in patients with an advanced pancreatic cancer.